An Innovative Risk-Reducing Approach to Postmastectomy Radiation Delivery after Autologous Breast Reconstruction. Issue 4 (April 2017) - Piper, Merisa L.; Evangelista, Maristella; Amara, Dominic; Daar, David; Foster, Robert D.; Fowble, Barbara; Sbitany, Hani
Abstract : Introduction: Postmastectomy radiation therapy (PMRT) has known deleterious side effects in immediate autologous breast reconstruction. However, plastic surgeons are rarely involved in PMRT planning. Our institution has adopted a custom bolus approach for all patients receiving PMRT. This offers uniform distribution of standard radiation doses, thereby minimizing radiation-induced changes while maintaining oncologic safety. We present our 8-year experience with the custom bolus approach for PMRT delivery in immediate autologous breast reconstruction. Methods: All immediate autologous breast reconstruction patients requiring PMRT after 2006 were treated with the custom bolus approach. Retrospective chart review was performed to compare the postirradiation complications, reconstruction outcomes, and oncologic outcomes of these patients with those of previous patients at our institution who underwent standard bolus, and to historical controls from peer-reviewed literature. Results: Over the past 10 years, of the 29 patients who received PMRT, 10 were treated with custom bolus. Custom bolus resulted in fewer radiation-induced skin changes and less skin tethering/fibrosis than standard bolus (0% vs 10% and 20% vs 35%, respectively), and less volume loss and contour deformities compared with historical controls (10% vs 22.8% and 10% vs 30.7%, respectively). Conclusions: Custom bolus PMRT minimizes radiation delivery to the internal mammary vessels, anastomoses, and skin; uniformly doses the surgical incision; and provides the necessary radiation dose to prevent recurrence. Because custom bolus PMRT may reduce the deleterious effects of radiation on reconstructive outcomes while maintaining safe oncologic results, we encourage all plastic surgeons to collaborate with radiation oncologists to consider this technique.